Rhetorical Moves of Research Article Abstracts Written by American and Indonesian Authors : Comparative Study - Nur Alfin Karimah; Ahmad Munir; Syafiul Anam (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2023)
As an indispensable part of the Research Article (RA), an abstract should be well written. The variability of information included in a research article abstract will likely vary because of different discourses among academicians worldwide.  This paper compares the rhetorical moves manifested in research article abstracts written by American and Indonesian authors published in two reputable journals. Data presented are move sequences of 25 Research Article (RA) abstracts from the latest six years issue (2022-2016). The abstracts were selected from a particular discipline, English language teaching and learning, to control the variability. Each move was identified based on the lexical used. The findings revealed that Move 1-Move 2-Move 3-Move 4-Move 5 and Move 2-Move 3-Move 4-Move 5 were the most salient move patterns found in both groups. Interestingly, abstracts of American authors showed cyclicity patterns and had an additional Move. Move 3 and Move 4 were considered as obligatory Moves, while Move 1 and Move 5 could be positioned as optional Moves. The study also found that American and Indonesian authors' writing styles differed. The implication of this study is expected to strengthen the theory of rhetorical moves in the literature. Also, it can be scientific evidence for Indonesian scholars to get a reference of how native academicians write their abstracts in reputable international journals